Influence of diode laser surface melting on microstructure and corrosion resistance of 7075 aluminium alloy. (2016) - Rao, A.C. Umamaheshwer; Vasu, V.; Shariff, S.M.; Srinadh, K.V. Sai
High power diode laser (HPDL) has been used for surface melting of 7075-T651 aluminium alloy in order to induce changes in the microstructure and corrosion performance. Laser surface melting was carried out using 4 kW power with the scan rate of 10 mm/s in the nitrogen atmosphere. The microstructural study shown that within the resolidified laser-melted layer, most of the coarse constituent particles and the original grain boundaries of the wrought structure were removed. The grain boundaries of the resolidified structure were observed to be free from precipitates. The corrosion studies of the alloy were determined by potentiodynamic polarisation measurements and electrochemical impedance spectroscopy measurements in 3.5% sodium chloride solution. It was observed that the corrosion rate was reduced by four times, when compared with the untreated sample. The superior corrosion resistance was attributed due to absence of detrimental Al-Cu-Fe constituent particles from the surface of laser-melted layer.